2022
DOI: 10.3390/cells11050772
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide 3 Kinase γ Plays a Critical Role in Acute Kidney Injury

Abstract: Inflammatory cells contribute to the pathogenesis of renal ischemia-reperfusion injury (IRI). However, the signaling mechanisms underlying the infiltration of inflammatory cells into the kidney are not well understood. In this study, we examined the effects of phosphoinositide 3 kinase γ (PI3Kγ) on inflammatory cells infiltration into the kidney in response to ischemia-reperfusion injury. Compared with wild-type mice, PI3Kγ knockout mice displayed less IRI in the kidney with fewer tubular apoptotic cell. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 43 publications
0
3
1
Order By: Relevance
“…AKT2 was reported involved in glucose metabolism and inhibiting apoptosis. 19 , 28 These three isoforms were not differentiated in this study. The insulin-activated P-AKT may inhibit the apoptosis of tubular epithelial cells through a decrease in the expression of Bax and cleaved caspase-3 in the nucleus.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…AKT2 was reported involved in glucose metabolism and inhibiting apoptosis. 19 , 28 These three isoforms were not differentiated in this study. The insulin-activated P-AKT may inhibit the apoptosis of tubular epithelial cells through a decrease in the expression of Bax and cleaved caspase-3 in the nucleus.…”
Section: Discussioncontrasting
confidence: 62%
“…Mice were subjected to renal IRI at 9:00 a.m., as previously reported. 19 Briefly, anesthesia was performed by intraperitoneal injections of esketamine (50 mg/kg) and dexmedetomidine (0.25 mg/kg). 20 The kidneys were exposed and subjected to ischemia by clamping renal pedicles with non-traumatic micro-aneurism clamps.…”
Section: Methodsmentioning
confidence: 99%
“…It was reported that PI3Kγ knockout attenuated kidney injury in an I/R-induced kidney injury mouse model. The PI3Kγ knockout mice had reduced levels of infiltrating neutrophils, macrophages, and T cells in the kidney samples and lowered levels of inflammation [48]. PI3Kγ could also mediate the inflow of macrophages, T cells, and fibroblasts into the kidney, leading to renal fibrosis and injury [49].…”
Section: Discussionmentioning
confidence: 99%
“…The vehicle-treated mice were subcutaneously injected with the same volume of normal saline as the insulin injection. IRI was performed on mice kidneys at 9:00 a.m., as previously reported [17]. Brie y, anesthesia was performed by intraperitoneal injections of esketamine (50 mg/kg) and dexmedetomidine (0.25 mg/kg) [18].…”
Section: Animalsmentioning
confidence: 99%